A comparative study of knowledge and practice regarding menstrual hygiene among private and government schools of Jaipur city - Sharma, Nikita; Meena, K. K.; Gaur, Kusum; Sharma, Dharmesh (International Journal Of Community Medicine And Public Health, 2019)
Background: Menstruation is a normal physiological process to the females but sometimes it is considered as unclean phenomenon in the society. Hence this community based study was carried out with the objective to assess the difference in level of knowledge and practice regarding menstrual hygiene among school going adolescent girls of government and private school. Methods: A community-based cross-sectional study was conducted from July 2017 to April 2018 to find out the difference in prevailing knowledge and practices regarding menstrual hygiene between private and government school going adolescent girls of Jaipur city. Data were collected by the predesigned and pretested structured questionnaire. Results: 87.57% girls from private schools were aware of menstruation prior to attainment of menarche. The difference in knowledge regarding menstruation in students of private and government school was significant. More than three fourth of the participants (76.95%) were from private school use sanitary pad. Conclusions: Knowledge and practice regarding menstruation was better in private school girls as compared to those of government school. Significantly more number of girls in the private schools was using sanitary pads as compared to government school girls.